ARBITRATION PRICING THEORY AS AN ANALYSIS TOOL IN EFFICIENT GROUPING OF STOCK - Azzahra, An Suci (Proceeding International Seminar of Islamic Studies, 2023)
The aims of this study are: (1) To be able to find out which stocks are efficient and inefficient using APT to avoid investment mistakes. (2) So that investors can understand APT to help investors determine the best investment decisions. The population of this research is 27 Business Indices for the 2019-2021 period. The sampling technique used was purposive sampling. The sample used in this study is the company's stock returns and consistently listed on the 27 Business Index for the 2019-2021 period. This study uses monthly closing stock price data, Business 27 Index data and SBI data, macro variable data consisting of inflation, the Rp/USD exchange rate, SBI interest rates, and the IHSG. The results showed that there were 9 efficiency stocks out of 16 stocks in the CAPM model, namely ADRO, ASII, BBCA, BBNI, BBRI, BMRI, INTP, PWON and TLKM